PENGARUH EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA MA DARUL ULUM ROUTA - Muh Safwan; Bambang Sampurno; Ratika Nengsih; Mustamin; Abdul Wahab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the relationship between parents economic conditions andstudents learning motivation at MA Darul Ulum Routa, Konawe, SoutheastSulawesi. Using a quantitative approach, data were collected through observation,documentation, and questionnaires. The results showed that most parents havelower to middle economic conditions (average score of 70.57 on a scale of 84),which is influenced by the level of education and the type of work that is generallyinformal. Nevertheless, most parents still support their childrens education. Ingeneral, students learning motivation is classified as moderate to high (average67.54 on a scale of 80), indicating quite good enthusiasm for learning, althoughsome students showed low motivation. Simple linear regression analysis showed asignificant effect (p=0.000) between parents economic conditions and learningmotivation (R²=0.645). This means that around 64.5% of the variation in learningmotivation can be explained by parents economic conditions, while the rest(35.5%) is influenced by other factors, including the learning environment, the roleof teachers, and students psychological factors. In conclusion, the economicconditions of the parents of students at MA Darul Ulum Routa are mostly middle tolower, while the students learning motivation is classified as medium-high. Theanalysis shows a significant positive correlation (64.5%) between the parentseconomy and learning motivation. However, factors outside the economy also playa crucial role. Further research needs to explore these factors for a morecomprehensive understanding.